FACTORS INFLUENCING THE SCHOOL CLIMATE AT INDONESIA SCHOOL OF KUALA LUMPUR (SIK), MALAYSIA - Muhajir Muhajir (STKIP Singkawang, 2017)
This study attempts to examine the factors influencing the school climate (Interaction, Facilities of school, and Feeling of Trust). The study used sample of 212 students of Indonesian School of Kuala Lumpur (SIK). The Confirmatory Factor Analysis (CFA) was conducted to investigate the correlation among the factors. The result of this study found the interrelated between the dimensions of school climate